Financial Governance and Strategic Planning for Sustainable NGO Operations (European Journal of Marketing and Economics, 2026)
Non-governmental organizations (NGOs) play a vital role in addressing societal challenges, yet their long-term viability depends critically on effective financial governance. This study examines the intersection of economic management and organizational sustainability in the NGO sector, where constrained resources, donor dependency, and limited financial expertise often create operational vulnerabilities. Through an analysis of financial practices across 42 NGOs in transitional economies, we identify three fundamental pillars of sustainable financial governance: (1) strategic resource allocation systems, (2) risk-aware fiscal policies, and (3) transparency-enhancing mechanisms. Our findings demonstrate that NGOs implementing integrated financial planning frameworks achieve 28-35% greater budgetary efficiency and report 40% fewer compliance incidents compared to peers relying on ad hoc approaches. Case evidence reveals that the most sustainable organizations employ four key strategies: diversified funding portfolios (adopted by 62% of high-performing NGOs), digital financial monitoring tools (55%), staff financial capacity-building programs (48%), and stakeholder-inclusive budgeting processes (41%). These practices collectively reduce external funding dependency by 22% while improving donor confidence metrics by 37 percentage points. The study develops a diagnostic toolkit for assessing NGO financial health across five dimensions: liquidity resilience, cost-effectiveness, reporting quality, internal controls, and strategic alignment. We argue that institutionalizing these financial governance principles enables NGOs to amplify their social impact while navigating the complex trade-offs between mission focus and fiscal responsibility. Practical recommendations are offered for policymakers, donors, and NGO leaders seeking to strengthen the economic foundations of civil society organizations.
Keywords: NGO sustainability, financial governance, nonprofit management, strategic budgeting, fiscal transparency, donor relations, resource optimization, organizational resilience